1999
DOI: 10.1007/s004360050499
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomal granuloma modulation. I. Schistosoma mansoni worm antigens CAA and CCA prime egg-antigen-induced hepatic granuloma formation

Abstract: Adult Schistosoma mansoni worms can positively modulate soluble egg antigen (SEA)-induced granulomas formed around SEA-coupled beads implanted in the liver. In this study, our aim was to further unravel the immunopathological characteristics of S.mansoni-worm-derived antigens in vivo. (a) Adult worm antigen (AWA)-coupled Sepharose beads, implanted into the liver, induced granulomas, containing numerous eosinophilic granulocytes and elicited marked periparticular fibrosis (composed of interstitial matrix protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The interpretation of immune reactions to the eggs is complicated by this previous exposure to antigens, including antigens cross-reactive with egg antigens (Lukacs & Boros 1991). Unisexually infected mice and mice sensitized to many worm antigens are also sensitized to egg antigens and have an augmented and accelerated response to injected eggs , Jacobs et al 1997a, 1998c, in unexplained contrast to the report of Warren and Domingo (1970).…”
mentioning
confidence: 59%
“…The interpretation of immune reactions to the eggs is complicated by this previous exposure to antigens, including antigens cross-reactive with egg antigens (Lukacs & Boros 1991). Unisexually infected mice and mice sensitized to many worm antigens are also sensitized to egg antigens and have an augmented and accelerated response to injected eggs , Jacobs et al 1997a, 1998c, in unexplained contrast to the report of Warren and Domingo (1970).…”
mentioning
confidence: 59%
“…It was demonstrated that live, adult S. mansoni worms could positively modulate egg-antigen-induced hepatic (Van Marck et al 1983;Jacobs et al 1997a) and pulmonary (Cheever et al 1997) granuloma formation. In addition, we recently showed that the gut-derived antigens CCA and CAA were able to prime egg-antigen-induced granuloma formation in the liver (Jacobs et al 1998). These ®ndings are consistent with the observation by Lukacs and Boros (1991) that prepatent S. mansoni infections sensitized for granuloma formation, and by Leptak and Mckerrow (1997) that schistosome egg granulomas and hepatic expression of tumour necrosis factor (TNF-a) are dependent on immune priming during parasite maturation prior to egg deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Since immunogenic carbohydrates are part of the molecular structure of the gut-associated antigens CCA and CAA, and because these schistosome gut antigens were capable of priming egg-antigen-induced hepatic granuloma formation in vivo (Jacobs et al 1998), we decided to investigate the modulatory capacity of systemically administered LewisX and LNFP-III molecules on egg-antigen-induced hepatic granuloma formation.…”
Section: Introductionmentioning
confidence: 99%
“…Monica C. Botelho, 1,2, * Paula A. Oliveira, 3 Paulo Vieira, 1 Maria de Lurdes Delgado, 1 Ligia Lourenço, 3 Carlos Lopes, 4,5 Jose C. Machado 2,6 and Jose M. Correia da Costa 1 exist between the host and the parasite. Parasite stage-specific factors as well as host organ-specific modalities and the genetic background have been identified or implicated in the pathogenesis of schistosomiasis.…”
Section: Granulomatous-like Immune Reaction and Hepatic Fibrosis Indumentioning
confidence: 99%
“…Schistosomal granuloma formation is generally considered to be the result of a delayed-type hypersensitivity response generated by the host toward antigens secreted by tissue-deposited parasite eggs. [3][4][5][6] Schistosomal egg granuloma formation and ensuing hepatic fibrosis are intriguing pathophysiological processes demonstrating the complex interactions that…”
Section: Introductionmentioning
confidence: 99%